Digital technology in words: Contemporary challenges for the french language - ABDELHAMID, Nabila; CHENNOUF, Aicha Lilia (Journal of Ecohumanism, 2025)
Digital technology is now omnipresent in our lives and daily routines. We are constantly surrounded by screens, and use digital technologies to communicate, work, entertain ourselves, stay informed, and more. This omnipresent of digital technology has a profound impact on society, our behavior, and even our relationships.The evolution of digital technologies has also affected our language and human communication, which are undergoing significant transformations. New digital tools allow us to communicate more quickly, easily, and accessibly way, creating linguistic challenges such as the spread of texting language, the use of abbreviations and Anglicisms, and the simplification of syntax.Faced with the growing ubiquity of digital technology in our daily lives, and by examining these changes, we will seek to understand how technological developments influence language and human communication, and what contemporary challenges emerge from this convergence between the digital world and our linguistic expression.